Otitis media with effusion in children younger than 1 year - Di Francesco,Renata Cantisani (2016)
Abstract Objective: To determine the prevalence of otitis media with effusion in children younger than 1 year and its association with the season of the year, artificial feeding, environmental and perinatal factors. Methods: Retrospective study of 184 randomly included medical records from a total of 982 healthy infants evaluated for hearing screening tests. Diagnosis of otitis media with effusion was based on otoscopy (amber-gold color, fluid level, handle of malleus position), type B tympanometric curves and absence of otoacoustic emissions. Incomplete medical records or those describing acute otitis media, upper respiratory tract infections on the assessment day or in the last 3 months, neuropathies and craniofacial anomalies were excluded. Data such as gestational age, birth weight, Apgar score, type of feeding and day care attendance were compared between children with and without otitis media with effusion through likelihood tests and multivariate analysis. Results: 25.3% of 184 infants had otitis media with bilateral effusion; 9.2% had unilateral. In infants with otitis media, the following were observed: chronological age of 9.6±1.7 months; gestational age >38 weeks in 43.4% and birth weight >2500g in 48.4%. Otitis media with effusion was associated with winter/fall, artificial feeding, Apgar score <7 and day care attendance. The multivariate analysis showed that artificial feeding is the factor most often associated to otitis media with effusion. Conclusions: Otitis media with effusion was found in about one third of children younger than 1 year and was mainly associated with artificial feeding.